Determinants of the Reliability of SKPD Financial Statements - Haryanto Haryanto (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2023)
This study aims to examine the reliability of SKPD financial statements. The Independent variable in this study consists of four variables that are: understanding of accrual-based government accounting standards (USAB), utilisation of information technology (UIT), internal control system (ICS), and human resource capacity (HRC). This research uses primary data from 32 SKPD in Semarang City, amounting to 84 respondents. Respondents in this study are 1 SKPD Financial Administration Officer (PPK-SKPD) and 2 Assistant Staff of the SKPD Financial Administration Officer at each SKPD. This research uses questionnaires using a Likert scale of 1-5. The results showed that the UIT has no significant favourable influence on the reliability of SKPD financial statements. While the USAB, ICS, and HRC significantly positively influence the dependent variable of the reliability of SKPD financial statements. Keywords: reliability, SKPD, financial statement.